Perspectives for regulating 10 nm particle number emissions based on novel measurement methodologies. (May 2022) - Samaras, Z.; Rieker, M.; Papaioannou, E.; van Dorp, W.F.; Kousoulidou, M.; Ntziachristos, L.; Andersson, J.; Bergmann, A.; Hausberger, S.; Keskinen, J.; Karjalainen, P.; Martikainen, S.; et al.
Abstract: Concerns regarding noxious emissions from internal combustion engines have increased over the years. There is a strong need to understand the nature of sub-23 nm particles and to develop measurement techniques to evaluate the feasibility of new regulations for particle number emissions in the sub-23 nm region (down to at least 10 nm). This paper presents the results of three EU-funded projects (DownToTen, PEMs4Nano and SUREAL-23) which supported the understanding, measurement and regulation of particle emissions below 23 nm and have successfully developed sub-23 nm particle measurement devices, specifically laboratory systems and mobile devices for RDE tests. The new technology was validated in chassis dyno tests and on the real road. The results show that sub-23 nm particles are mainly generated at the engine start and during acceleration phases. The innovations show that the technology is mature and robust enough to serve as a basis for regulating sub-23 nm particles. Highlights: Sub-23 nm particle measurement devices have been developed. Tests show that solid particles of 10 nm and larger can be reliably counted. Sub-23 nm particles are mainly generated at engine start and during acceleration. The chemical composition of sub-23 nm particles is size-dependent.